MANAJEMEN KINERJA - Berliana Putri; Najmudin; Machdum Bachtiar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to comprehensively analyze the performance management system, including performance planning, organizing, monitoring, evaluation, and performance development within organizations. The research employs a library research approach by reviewing relevant scientific literature related to performance management concepts and practices. The findings indicate that organizational performance effectiveness is strongly influenced by clear goal setting, structured task allocation, systematic monitoring mechanisms, and objective and continuous evaluation systems. Furthermore, performance development through training, coaching, and constructive feedback plays a crucial role in enhancing human resource competencies. The integration of all stages of performance management in a coherent and systematic manner contributes to the creation of a productive, accountable, and adaptive work culture in response to environmental changes. Therefore, the implementation of a well-structured performance management system becomes a key strategy for improving organizational competitiveness and long-term sustainability